High myopia as risk factor for the 10-year incidence of open-angle glaucoma in the Beijing Eye Study: clinical science - Wang, Ya Xing; Yang, Hua; Wei, Chuan Chuan; Xu, Liang; Wei, Wen Bin; Jonas, Jost B. (British journal of ophthalmology, 2023)
Purpose To assess the 10-year incidence of open-angle glaucoma (OAG) and its associations in an adult Chinese population. - Methods Longitudinal observational population-based study. Out of 4439 participants aged 40+ years participating in the Beijing Eye Study in 2001, 2695 individuals (60.7%) were re-examined in 2011, while 397 participants had died (8.5%). - Results Incident OAG was found in 75 participants among 2494 individuals free of glaucoma at baseline. The 10-year OAG incidence (mean: 3.0%; 95% CI 2.5 to 3.5) increased from 1.8% (95% CI 1.3 to 2.4) in individuals aged 40-49 years, to 5.9% (95% CI 3.1 to 9.6) in participants aged 70+ years. OAG incidence was highest in the high myopia group (13.3%±6.3%, OR: 7.3; 95% CI 3.3 to 16.3), followed by the moderately myopic group (8.1%±4.3%, OR: 4.2; 95% CI 2.0 to 8.8) and the low myopic group (6.2%±2.8%, OR: 3.2; 95% CI 1.7 to 5.8), as compared with the emmetropic/hyperopic group (2.1%±0.8%). In multivariable analysis, higher OAG incidence was associated with older age (OR: 1.06; 95% CI 1.03 to 1.09), longer axial length (OR: 1.72; 95% CI 1.45 to 2.05), higher intraocular pressure (IOP) in 2001 (OR: 1.18; 95% CI 1.08 to 1.29), higher vertical cup/disc ratio (VCDR) (OR: 60.8; 95% CI 6.7 to 556) and thinner central corneal thickness (CCT) (OR: 0.98; 95% CI 0.97 to 0.99). - Conclusions In a 10-year follow-up, high myopia was a major risk factor for the development of OAG with a 7.3-fold risk increase as compared with emmetropic eyes. Higher age, IOP, VCDR and thinner CCT were additionally related with an increased OAG incidence. The findings may be of importance to clinical protocols and screening strategies.